To the 20th anniversary of the journal BIOpreparations. Prevention, Diagnosis, Treatment - O. Yu. Goikalova; E. V. Lebedinskaya; A. P. Shestakova (Биопрепараты: Профилактика, диагностика, лечение, 2021)
.